RETRACTION Alnedral, A., Jatra, R.., Firdaus, K.., Neldi, H., Bakhtiar, S.., Damrah, D., Masrun, M., Aldani, N., Yendrizal, Y., Ockta, Y., & Festiawan, R.. (2024). El efecto de un modelo de entrenamiento con enfoque holístico en el aumento de la velocidad y la agilidad en los atletas de tenis. Retos, 61, 1138–1145. https://doi.org/10.47197/retos.v61.108915 - RETOS, RETOS (Retos, 2025)
Alnedral, A., Jatra, R.., Firdaus, K.., Neldi, H., Bakhtiar, S.., Damrah, D., Masrun, M., Aldani, N., Yendrizal, Y., Ockta, Y., & Festiawan, R.. (2024). El efecto de un modelo de entrenamiento con enfoque holístico en el aumento de la velocidad y la agilidad en los atletas de tenis. Retos, 61, 1138–1145. https://doi.org/10.47197/retos.v61.108915 Retraction of the article by the editor of the journal. There has been several clear and conclusive proofs that there has been a manipulation of the authorship of the article. The accepted Word document was sent with the names of the authors that appeared in the “Corrections for the edition” message so that they could only make the orthographical corrections that were necessary. The corresponding author (or whoever hurt him) changed the authors of the aforementioned Word document that was sent to them, returning a document together with these corrections made with new authors, all without any express notification, without any document explaining the changes made accepted by all the authors and, of course, without express authorization from the journal Retos between both moments. With this fraudulent document the galleys were made and the article was definitively published, assigning it the corresponding DOI. Authors in the Word document of the article submitted for review: 5 Authors in the published PDF with modified authors: 11 Differences between the authors between both moments: +6 (Hendri Neldi, Syahrial Bakhtiar, Damrah, Masrun, Nissa Aldani, Yendrizal Yendrizal)